East Asia Update, November 2005 : Countering Global Shocks - World Bank (Washington, DC, 2013)
Growth in the Emerging East Asia region is expected to reach a little over 6 percent in 2005, down modestly from the exceptionally strong 7.2 percent pace of 2004. One of the clearly most fortunate developments of the last two years is the unexpectedly limited effect on economic growth of the more than doubling of crude oil prices. Several governments have had the political confidence and credibility with the public to implement politically sensitive cuts in or removal of subsidies on fuel products, allowing fuel users to respond more effectively to signals from world markets. Central banks in the region have also been tightening monetary policy to prevent the rise in oil prices and headline inflation from becoming embedded in higher trend rates of core price and wage inflation. While the tightening cycle may tend to moderate the cyclical recovery in domestic demand in the region in the near term, it will, by helping ensure moderate inflation and macroeconomic stability, also help promote more sustainable growth in the medium term. International trade has long been a great source of productivity gains and growth in East Asia. Last year's over 10 percent gain in world trade was paced by a 15-20 percent gain in East Asian real exports and imports. The Special Focus in this Update on What can East Asia Expect from the Doha Development Round? looks in more detail at the issues at stake for the region. Last but very far from least is the risk from avian influenza, which, if it expands to a widespread human influenza, could exact a dreadful toll in human life and economic losses both in Asia and around the world. The threat and the urgent policy responses that are needed are discussed later in this report.